MicroRNAs as Immune Regulators of Inflammation in Children with Epilepsy - Abdel Raouf, Haiam (Int J Mol Cell Med, 2020)
Epilepsy is a chronic clinical syndrome of brain function which is caused by abnormal discharge of neurons. MicroRNAs (miRNAs) are small non-coding RNAs which act post-transcriptionally to regulate negatively protein levels. They affect neuroinflammatory signaling, glial and neuronal structure and function, neurogenesis, cell death, and other processes linked to epileptogenesis. The aim of this study was to explore the possible role of miR-125a and miR-181a as regulators of inflammation in epilepsy through investigating their involvement in the pathogenesis of epilepsy, and their correlation with the levels of inflammatory cytokines. Thirthy pediatric patients with epilepsy and 20 healthy controls matched for age and sex were involved in the study. MiR-181a and miR-125a expression were evaluated in plasma of all subjects using qRT-PCR. In addition, plasma levels of inflammatory cytokines (IFN-γ and TNF-) were determined using ELISA. Our findings indicated significantly lower expression levels of miR-125a (P=0.001) and miR-181a (P=0.001) in epileptic patients in comparison with controls. In addition, the production of IFN-γ and TNF- was non-significantly higher in patients with epilepsy in comparison with the control group. Furthermore, there were no correlations between miR-125a and miR-181a with the inflammatory cytokines (IFN-γ and TNF-) in epileptic patients. MiR-125a and miR-181a could be involved in the pathogenesis of epilepsy and could serve as diagnostic biomarkers for pediatric patients with epilepsy.